Prevalence of Plasmodium falciparum Pfcrt and Pfmdr1 alleles in settings with different levels of Plasmodium vivax co-endemicity in Ethiopia. (December 2019) - Hailemeskel, Elifaged; Menberu, Temesgen; Shumie, Girma; Behaksra, Sinknesh; Chali, Wakweya; Keffale, Migbaru; Belachew, Mulualem; Shitaye, Getasew; Mohammed, Hussien; Abebe, Daniel; Ashine, Temesgen; Drakeley, Chris; et al.
Abstract: Plasmodium falciparum and P. vivax co-exist at different endemicity levels across Ethiopia. For over two decades Artemether-Lumefantrine (AL) is the first line treatment for uncomplicated P. falciparum, while chloroquine (CQ) is still used to treat P. vivax . It is currently unclear whether a shift from CQ to AL for P. falciparum treatment has implications for AL efficacy and results in a reversal of mutations in genes associated to CQ resistance, given the high co-endemicity of the two species and the continued availability of CQ for the treatment of P. vivax . This study thus assessed the prevalence of Pfcrt -K76T and Pfmdr1 -N86Y point mutations in P. falciparum. 18S RNA gene based nested PCR confirmed P. falciparum samples (N = 183) collected through community and health facility targeted cross-sectional surveys from settings with varying P. vivax and P. falciparum endemicity were used. The proportion of Plasmodium infections that were P. vivax was 62.2% in Adama, 41.4% in Babile, 30.0% in Benishangul-Gumuz to 6.9% in Gambella. The Pfcrt- 76T mutant haplotype was observed more from samples with higher endemicity of P. vivax as being 98.4% (61/62), 100% (31/31), 65.2% (15/23) and 41.5% (22/53) in samples from Adama, Babile, Benishangul-Gumuz and Gambella, respectively. However, a relatively higher proportion of Pfmdr1 -N86 allele (77.3–100%) were maintained in all sites. The observed high level of the mutant Pfcrt- 76T allele in P. vivax co-endemic sites might require that utilization of CQ needs to be re-evaluated in settings co-endemic for the two species. A country-wide assessment is recommended to clarify the implication of the observed level of variation in drug resistance markers on the efficacy of AL-based treatment against uncomplicated P. falciparum malaria. Graphical abstract: Image 1